First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Hunting, non-timber forestry products, and jaguars (Panthera onca): How livelihoods influence views toward jaguars in protected areas of the Bolivian Amazon - Andre Becker; Nuno Negrões; María Díez-León; Indyra Lafuente-Cartagena; Nelly Guerra; Daniel Larrea-Alcázar; Valeria Boron; Melissa Arias; Lila Sainz; Michelle Peñaranda; Bernarda Sanabria; Jenny Anne Glikman (Journal for Nature Conservation, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

A global blueberry phylogeny: Evolution, diversification, and biogeography of Vaccinieae (Ericaceae) - Anna L. Becker; Andrew A. Crowl; James L. Luteyn; Andre S. Chanderbali; Walter S. Judd; Paul S. Manos; Douglas E. Soltis; Stephen A. Smith; Deise J.P. Goncalves; Christopher W. Dick; William N. Weaver; Pamela S. Soltis; et al. (Molecular Phylogenetics and Evolution, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Mapping global cropland and field size - Steffen Fritz; Linda See; Ian McCallum; Liangzhi You; Andriy Bun; Elena Moltchanova; Martina Duerauer; Fransizka Albrecht; Christian Schill; Christoph Perger; Petr Havlik; Aline Mosnier; et al. (Global Change Biology, 2015)
A new 1 km global IIASA ‐ IFPRI cropland percentage map for the baseline year 2005 has been developed which integrates a number of individual cropland maps at global to regional to national scales. The individual map products include existing global land cover maps such as GlobCover 2005 and MODIS v.5, regional maps such as AFRICOVER and national maps from mapping agencies and other organizations. The different products are ranked at the national level using crowdsourced data from Geo‐Wiki to create a map that reflects the likelihood of cropland. Calibration with national and subnational crop statistics was then undertaken to distribute the cropland within each country and subnational unit. The new IIASA ‐ IFPRI cropland product has been validated using very high‐resolution satellite imagery via Geo‐Wiki and has an overall accuracy of 82.4%. It has also been compared with the EarthStat cropland product and shows a lower root mean square error on an independent data set collected from Geo‐Wiki. The first ever global field size map was produced at the same resolution as the IIASA ‐ IFPRI cropland map based on interpolation of field size data collected via a Geo‐Wiki crowdsourcing campaign. A validation exercise of the global field size map revealed satisfactory agreement with control data, particularly given the relatively modest size of the field size data set used to create the map. Both are critical inputs to global agricultural monitoring in the frame of GEOGLAM and will serve the global land modelling and integrated assessment community, in particular for improving land use models that require baseline cropland information. These products are freely available for downloading from the http://cropland.geo-wiki.org website.

Nitrogenous and phosphorus excretions in juvenile silver catfish (Rhamdia quelen) exposed to different water hardness, humic acid, and pH levels - Jaqueline Ineu Golombieski; Gessi Koakoski; Alessandra Janaína Becker; Ana Paula Gottlieb Almeida; Cândida Toni; Isabela Andres Finamor; Maria Amália Pavanato; Tielle Moraes de Almeida; Bernardo Baldisserotto (Fish Physiology and Biochemistry, 2013)

Haemodynamic adaptation during sudden gravity transitions - Jiexin Liu; Bart Verheyden; Frank Beckers; Andre E. Aubert (European Journal of Applied Physiology, 2012)